Intergenerationality and Zone of Imminent Development - ZDI: Points of intersection in the digital literacy of people with visual disabilities (Revista Contexto & Educação, 2026)
The present study offers contributions to the understanding of the learning dynamics between different age groups of people with visual impairment - PWD, highlighting the importance of digital technological accessibility. When addressing Intergenerationality and the Zone of Imminent Development (ZDI), the research shows that the exchange of knowledge and experiences between young people, adults and elderly people can enrich the educational process, especially in a school context.  The use of a qualitative approach, with techniques such as document analysis, participant observation and semi-structured interviews, allowed us to delve deeper into the experiences of fourteen participating students. Data categorization, through content analysis, made it possible to identify nuances in interactions and learning that occur in the intergenerational environment. The application of the ZDI concept showed that intergenerational relationships contribute to the development of older generations, improving their technological skills and knowledge.  The study reinforces that promoting an intergenerational and accessible environment can improve the learning experience of students with visual impairments, as well as create greater social and technological inclusion, preparing them for everyday challenges. The research points to the need for strategies that encourage this exchange of knowledge, evolving more collaborative and enriching teaching.
Keywords: Visual Impairment; Intergenerationalit; ZDI; Technology; Elderly Person